Analysis of Healthcare Service Quality Based on Patient Satisfaction at Ghaniya Clinic, Medan - Nurliati Nurliati; Reny Juliana Sihombing (Journal of Innovative and Creativity, 2026)
Background: Healthcare service quality is a critical determinant of patient satisfaction and clinic performance, particularly in primary healthcare settings in developing countries. Patient satisfaction serves as a key indicator to assess whether healthcare providers meet patients' expectations and needs. Objective: This study aims to analyze the quality of healthcare services based on patient satisfaction at Ghaniya Clinic, Medan, North Sumatra, Indonesia, using the SERVQUAL model encompassing five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Methods: A descriptive-analytical cross-sectional study was conducted from September to December 2025. A total of 150 outpatients were recruited using purposive sampling. Data were collected using a validated structured questionnaire based on the SERVQUAL instrument. Descriptive statistics, Customer Satisfaction Index (CSI), and Importance-Performance Analysis (IPA) were employed. Results: The overall patient satisfaction rate was 72.7%. Empathy scored the highest mean satisfaction (3.82 ± 0.51), while tangibility received the lowest score (3.41 ± 0.64). The Customer Satisfaction Index (CSI) was 76.3%, indicating a "Satisfied" category. IPA analysis revealed that responsiveness and physical facilities were the primary priority improvement areas. Conclusion: Healthcare service quality at Ghaniya Clinic is moderately satisfactory. Significant improvements are required in responsiveness and tangibility dimensions to achieve higher patient satisfaction. Systematic management interventions targeting staff responsiveness training and facility upgrading are strongly recommended.